PERAN LAYANAN MANASIK UMRAH EKSKLUSIF DALAM MENINGKATKAN KUALITAS IBADAH JAMAAH DI SAHELIA UMRAH DAN HAJJ SURABAYA - UciSilviatus Silviatus (J-MD Jurnal Manajemen Dakwah, 2025)
The increasing demand for Umrah services has encouraged travel organizers to enhance service quality, particularly through comprehensive manasik guidance that supports pilgrims’ spiritual and practical readiness. This study aims to examine and analyze the role of Exclusive Umrah Manasik services implemented by Sahelia Umrah and Hajj Surabaya in improving the quality of pilgrims’ worship. Employing a descriptive qualitative research design, data were collected through in-depth interviews, participant observation, and documentation involving staff members and pilgrims. The data were analyzed using the interactive model of Miles and Huberman, while data validity was ensured through technique and source triangulation. The findings reveal that the Exclusive Umrah Manasik program is implemented through structured online and offline stages, integrating technical ritual instruction, direct practice guided by experienced muthawwif, and exclusive spiritual development sessions. The program is supported by adequate facilities, professional instructors, and additional service innovations that enhance pilgrims’ comfort and preparedness. Furthermore, the implementation of this program reflects key service quality dimensions, including reliability, responsiveness, assurance, empathy, and tangibles, all of which contribute significantly to strengthening pilgrims’ spiritual, mental, and technical readiness. Despite these strengths, challenges remain in the form of varying levels of pilgrims’ understanding and occasional non-compliance with scheduled activities. In conclusion, the Exclusive Umrah Manasik services provided by Sahelia Umrah and Hajj play a crucial role in enhancing the quality of pilgrims’ worship by fostering deeper spiritual awareness, confidence, and ritual accuracy. This study contributes to the literature on religious service management by highlighting the importance of personalized and spiritually oriented manasik guidance. Future research is recommended to involve multiple Umrah service providers and employ mixed-method approaches to broaden the scope and generalizability of the findings.